Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 7 - Exponents and Exponential Functions - 7-3 Multipying Powers with the Same Base - Practice and Problem-Solving Exercises - Page 430: 63


$-12x^6 + 40x^4$

Work Step by Step

(i) $a^m \cdot a^n = a^{m+n}$ (ii) $x(y-z) = xy - xz$ Use rule (ii) above by multiplying $-4x^3$ to each term of the binomial to obtain: $=-4x^3(3x^3) - (-4x^3)(10x)$ Multiply the coefficients together, and then apply rule (i) above to obtain: $\\=-12x^{3+3}-(-40x^{3+1}) \\=-12x^6-(-40x^4) \\=-12x^6 + 40x^4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.